Does Increasing Women's Schooling Raise the Schooling of the Next Generation? Comment - Antonovics, Kate L; Goldberger, Arthur S (American Economic Review, 2005)
“Does increasing women's schooling raise the schooling of the next generation?” is the question posed by Jere R. Behrman and Mark R. Rosenzweig (2002). Their answer to the question is no. In fact, they conclude that raising women's schooling may lower the schooling of the next generation. We show that Behrman and Rosenzweig's results are not robust to alternative coding schemes and sample selection rules, and argue that their policy inference may be misguided.